Microbial diversity in a Venezuelan orthoquartzite cave is dominated by the Chloroflexi (Class Ktedonobacterales) and Thaumarchaeota Group I.1c - Barton, Hazel A.; Giarrizzo, Juan G.; Suarez, Paula; Robertson, Charles E.; Broering, Mark J.; Banks, Eric D.; Vaishampayan, Parag A.; Venkateswaran, Kasthisuri (Frontiers in Microbiology, 2014)
The majority of caves are formed within limestone rock and hence our understanding of cave microbiology comes from carbonate-buffered systems. In this paper, we describe the microbial diversity of Roraima Sur Cave, an orthoquartzite (SiO4) cave within Roraima Tepui, Venezuela. The cave contains a high level of microbial activity when compared with other cave systems, as determined by an ATP-based luminescence assay and cell counting. Molecular phylogenetic analysis of microbial diversity within the cave demonstrate the dominance of Actinomycetales and Alphaproteobacteria in endolithic bacterial communities close to the entrance, while communities from deeper in the cave are dominated (82-84%) by a unique clade of Ktedonobacterales within the Chloroflexi. While members of this phylum are commonly found in caves, this is the first identification of members of the Class Ktedonobacterales. An assessment of archaeal species demonstrates the dominance of phylotypes from the Thaumarchaeota Group I.1c (100%), which have previously been associated with acidic environments. While the Thaumarchaeota have been seen in numerous cave systems, the dominance of Group I.1c in Roraima Sur Cave is unique and a departure from the traditional archaeal community structure. Geochemical analysis of the cave environment suggests that water entering the cave, rather than the nutrient-limited orthoquartzite rock, provides the carbon and energy necessary for microbial community growth and subsistence, while the poor buffering capacity of quartzite or the low pH of the environment may be selecting for this unusual community structure. Together these data suggest that pH, imparted by the geochemistry of the host rock, can play as important a role in niche-differentiation in caves as in other environmental systems.